Decision Support System For Scholarship Candidate Selection - Lailatul Qodriyah, Emilyati; Dwi Cahyono; Ratna Nur Tiara Shanty (CV.RIZANIA MEDIA PRATAMA, 2025)
System used by the university. Soetomo surabaya for the selection of prospective students who are eligible to receive a scholarship is still using the manual way. Given the enormous number of submissions by scholarship recipients will make it difficult for universities in selecting students who are eligible to receive scholarships. Therefore it is necessary that there is a system that can be used as supporting decision-making to determine the students who are eligible to get a scholarship at the University Dr Soetomo Surabaya in order to facilitate the University. The problem that occurs is the absence of a system used for the selection process of scholarship recipients at Dr. University. Soetomo Surabaya. This selection is done using Analytical Hierarcy Process (AHP) method, it will simplify the way the system to perform the selection, the work concept of Analytical Hierarcy Process (AHP) is able to determine the best alternative choice in determining a goal. Analytical Hierarcy Process (AHP) will determine the right student to get a scholarship viewed from several attributes that exist. With this decision support system, it will facilitate the University's work to determine the students who are eligible for a scholarship in terms of some existing attributes. The result of this decision support system is the obtaining of scholarship recommendation data in the form of value with percent form where this value which will be the management consideration to determine the scholarship recipient.